The Learning of Mathematics Based on Individual Differences : A Topic Trend Bibliometric Analysis Using VOSviewer - M.J. Dewiyani Sunarto; Julianto Lemantara (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to establish a foundation for the development of differentiated learning through an analysis of trends in articles related to personality type differences in the field of mathematics education. The research method used was descriptive, using Bibliometric Analysis. These 422 data from Scopus have been from Scopus-indexed journals and were obtained by defining search keywords, namely